An Analysis of Fairness and Quality Issues in Online Assessment at Higher Education in Pakistan - Uzair-ul-Hassan, Muhammad; Zaytouni, Anas (Pakistan Journal of Humanities and Social Sciences, 2023)
Remote assessment during pandemic Covid-19 had remained a big challenge for higher education institutions (Cooper & Tschobotko, 2020). Many issues related to fairness and quality in particular needed to be resolved (UNESCO, 2020). The study, thus, attempted to address in detail, quality and fairness issues associated with online formative and summative assessment at higher education. The study opted for a questionnaire including fixed-choice items as well as extended response questions. Undergraduate students (n=323) from higher education were population of the study. Quantitative data of students were analyzed through mean scores, percentages, t-test and ANOVA, whereas extended responses of students were analyzed through thematic analysis. Results revealed that online assessment at higher education seemed to be unsatisfactory whether related to fairness and quality in formative assessment as well as summative assessment. Formative assessments lacked in quality in terms of low quality assessments for students’ knowledge and practical skills; and unfair in terms of biasness and unfair award of marks. Online summative assessments lacked in quality test-construction, exacerbated by security and cheating threats. Other than that, teachers lacked in methodology, punctuality and teaching with responsibility during online education. Also, it was found that females were more sufferers of online assessment as compared to male students. Overall, online formative assessment and summative assessment whether in terms of fairness and/or quality had been unsatisfactory and many issues related to fairness and quality remained untouched which have serious implications in online education leading to face to face education and assessment system at large.